Gastric schwannoma with post-surgical gastroparesis: a case report and literature review - Miao, Ganggang; Zhang, De; Li, Jiajing; Deng, Yanxiang; Gu, Xingwei; Feng, Tingting (Frontiers in Oncology, 2025)
Gastric schwannoma is a relatively rare submucosal mesenchymal tumor with low probability of metastasis and arises from Schwann cells of the gastrointestinal nervous plexus. Surgical therapy is the main treatment of gastric schwannoma with symptoms or malignant tendency. Gastroparesis is a potential complication following gastrointestinal surgery, which is a clinical syndrome caused by gastric emptying disorder and characterized by nausea, vomiting, and bloating, resulting in insufficient nutrient intake. Generally, post-surgical etiology is the main potential etiology of gastroparesis, while the most common underlying etiology is diabetes mellitus. So far, reports of gastroparesis arising from resection of gastric schwannoma are rare. We present an 80-year-old woman who was diagnosed with gastrointestinal stromal tumor (GIST) primarily and has undergone laparoscopic wedge-shaped gastrectomy. The pathological and immunohistochemical examination ultimately established the diagnosis of gastric schwannoma. The patient experienced belching, nausea, vomiting, and bloating 1 week after the surgery and confirmed as gastroparesis through gastrointestinal series and gastroscopic examination. A series of treatments were performed, including correcting fluid-electrolyte disorders and vitamin deficiencies, and nutritional support and pharmacological treatments. The patient ultimately recovered well, and the relevant literatures were reviewed to identify and handle similar cases hereafter.